Physiological Classification of Sports Exercises - Utepbergenov Amangeldi Kutlimuratovich (Research Parks Publishing LLC, 2021)
The physiological classification of sports exercises is covered in this article. This is evidenced by a comparative study of the health of athletes of different qualifications, followed by many years of dynamic monitoring of leading athletes. This means that the size of the load is not a factor. The main thing is that it corresponds to the state of the organism and the level of readiness, because the effect of any stimulus is determined not only by its strength, but also by the ratio of the initial level of readiness.